Production of 415-ton ingots for backup rolls in the conditions of PJSC "Energomashspetsstal" - Efimov, Maxim Victorovich; Ryabtsev, Anatoliy Danilovich; Selyutin, Olexandr Andreevich; Troyanskyy, Oleksandr Anatolievich; Yavtushenko, Pavel Michaylovich; Pashynskyi, Volodymyr Victorovich (Vojnotehnički glasnik / Military Technical Courier, 2013)
The paper gives the results of work on melting, pouring, forging and heat treatment of 415-ton 45H3M1F steel ingots as semiproducts for manufacturing large backup rolls at the request of  «Severstal» Company. For the production of rollers, a new grade of steel based on 0.45%С and 3%Cr, additionally alloyed by Mo and V, was developed in PJSC «Energomashspetsstal» and applied in industry. Steel of bainite class provides the best combination of strength and plasticity properties. Metal was prepared by melting 7 heats in arc steel-melting furnaces with the capacity of 100 and 50 tons with subsequent out-of-furnace treatment on ladle – furnace and ladle – degassing units. The pouring of steel was carried out from four steel-pouring ladles into a vertical mould under vacuum through a tundish ladle with the protection of stream by argon. The forging of ingots was conducted on the automated 150MN forging system. The obtained billets were exposed to primary heat treatment which consisted of heating for recrystallization, isothermal soaking, in order to provide the removal of residual stresses, additional dehydrogenization to give the material lower hardness and controlled cooling for the prevention of snowflake formation. Heating of ingots for forging and preliminary heat treatment was carried out in heat treatment furnaces with the carrying capacity of up to 500 tons. For the heat treatment of the backup roll, a horizontal sprayer unit was applied. The tooling of the backup roll was executed on a lathe with one pace-plate and the final mechanical treatment was conducted on the machine-tool of Hercules NWD 1500×18000 CNC. Finished products with 225-ton mass of the following dimensions: a barrel with a diameter and a length of 2,360 mm and 4,800 mm, respectively, at a general length of 10,650 mm were obtained.
Keywords: non-metallic inclusions; rollers; casting; pouring; melting; technology; 415 ton; ingot